Growth of Candida sp and Aspergillus sp from Bronchoscopy Pulmonary Tuberculosis Patients on Bran Media - Mujahidah Basarang; Muhammad Rifo Rianto (Universitas Hasanuddin, 2018)
Pulmonary tuberculosis caused by Mycobacterium tuberculosis become ahealth problem in Indonesia. The chronic nature of this disease is further exacerbated ifit is accompanied by fungal infection such as Candida albicans and Aspergillus sp.,which is usually remains undiagnosed and thus untreated. Culture techniques can beused to identify Candida sp and Aspergillus sp from bronchoscopy. Fungal culturemedia in laboratory containing high carbohydrate source, nitrogen source are requiredfor the growth. This nutrient can be found in bran that contains high carbohydrates,proteins, fats, vitamins, and crude fiber. So that bran can be used as raw material for alternative fungal growth media. The purpose of this study was to increase bran as amedium for the growth of Candida sp and Aspergillus sp isolated from bronchoscopy ofpulmonary TB patients. This study included bran collection, preparation of bran media,inoculation bronchoscopy on bran media, observation of fungal growth. Colonies ofCandida sp and Aspergillus sp were confirmed microscopically. The results showed thatCandida sp and Aspergillus sp grew on both media, Bekatul Dextrose Agar and PotatoDextrose Agar. The conclusion of this study is that bran can be used as a medium forfungal growth. Bran media can be used as an alternative media to replace syntheticmedia to grow Candida sp and Aspergillus sp isolated from bronchial rinses.